CARIFIS Legacy Mission report July 1st-12th, 2004 - Medley, Paul (CRFM Secretariat Belize CityBZ, 2004)
Reports on efforts to test the routines necessary to transfer data from the old Trip Interview Programme (TIP) and Licensing and Registration System (LRS) databases to the Caribbean Fisheries Information System (CARIFIS).